2008
DOI: 10.1128/jb.00093-08
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of theShigella flexneriAutotransporter IcsA Reveals Novel Functional Regions Involved in IcsA Biogenesis and Recruitment of Host Neural Wiscott-Aldrich Syndrome Protein

Abstract: The IcsA (VirG) protein of Shigella flexneri is a polarly localized, outer membrane protein that is essential for virulence. Within host cells, IcsA activates the host actin regulatory protein, neural Wiskott-Aldrich syndrome protein (N-WASP), which in turn recruits the Arp2/3 complex, which nucleates host actin to form F-actin comet tails and initiate bacterial motility. Linker insertion mutagenesis was undertaken to randomly introduce 5-amino-acid in-frame insertions within IcsA. Forty-seven linker insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 56 publications
6
81
0
Order By: Relevance
“…Consistent with this hypothesis, large endogenous AT passengers appear to have stricter requirements for efficient secretion than small heterologous passengers (6,51). For example, secretion of IcsA is compromised by mutations in the C-terminal end of the endogenous passenger (52), whereas substituting the entire passenger for the smaller heterologous MalE protein results in efficient secretion (43).…”
Section: Discussionmentioning
confidence: 82%
“…Consistent with this hypothesis, large endogenous AT passengers appear to have stricter requirements for efficient secretion than small heterologous passengers (6,51). For example, secretion of IcsA is compromised by mutations in the C-terminal end of the endogenous passenger (52), whereas substituting the entire passenger for the smaller heterologous MalE protein results in efficient secretion (43).…”
Section: Discussionmentioning
confidence: 82%
“…This AC domain is conserved among many ATs, including members of the SPATE (for serine protease autotransporters of Enterobacteriaceae) subfamily to which Hbp belongs (22). Deletion and mutagenesis experiments have shown that this region is crucial for efficient folding of several passenger domains (23)(24)(25)(26). Recent evidence indicates that translocation of the passenger across the OM occurs in an C-to-N direction, possibly following the formation of a hairpin structure by the C terminus of the passenger in the ␤-domain channel (27,28).…”
mentioning
confidence: 99%
“…Indeed, heterologous expression of IcsA506-620-GFP fusion proteins has frequently been used to study the nature of spatial protein targeting in bacteria (Fixen et al, 2012;Janakiraman et al, 2009). However, in previous mutagenesis studies of full-length IcsA, we have found that insertions (5 aa linkers) within the nPT region (positions i56, i81 and i87) were unable to perturb PT, whilst insertions within the cPT region (positions i532 and i563) dramatically perturbed PT, resulting in circumferential distribution on the surface of bacteria (May & Morona, 2008). These data indicate that the cPT regions plays a more significant role in IcsA PT.…”
Section: Introductionmentioning
confidence: 78%
“…Polyclonal rabbit anti-N-WASP and polyclonal rabbit anti-IcsA were produced and validated as described previously (May & Morona, 2008;Van den Bosch et al, 1997). Monoclonal mouse anti-DnaK antibody was from Enzo Life Sciences.…”
Section: R564amentioning
confidence: 99%